The level of microRNA 21 is upregulated by rapamycin in serum of tuberous sclerosis complex patients and subependymal giant cell astrocytoma (SEGA)-derived cell cultures - Kuzniewska, Bozena; Sadowski, Krzysztof; Urbanska, Katarzyna; Urbanska, Malgorzata; Kotulska, Katarzyna; Liszewska, Ewa; Grajkowska, Wieslawa; Jóźwiak, Sergiusz; Dziembowska, Magdalena (Folia Neuropathologica, 2018)
Tuberous sclerosis complex (TSC) represents a genetic condition, in which the clinical manifestations are caused by the disinhibition of the mammalian target of rapamycin (mTOR) pathway due to mutations in the TSC1 (hamartin) or TSC2 (tuberin) genes. The deregulated mTOR activity leads to multi-site tumors, including subependymal giant cell astrocytoma (SEGA). SEGA is a brain tumor that affects around 15% of TSC patients. The aim of the study was to evaluate miR-21 expression in the serum of two groups of TSC patients: with or without SEGA tumors. We found no differences in the level of miR-21 depending on the presence of SEGA. Next, we studied the influence of prolonged rapamycin administration on miR-21 level in the blood serum of TSC patients (6-12 months of rapamycin) and in primary cultures of SEGA-derived cells treated with rapamycin in vitro . Here we show that rapamycin treatment leads to the upregulation of miR-21 in both patients’ serum and in primary SEGA tumor cells in the culture indicating the regulatory relationship between rapamycin treatment and miR-21 expression.